PO.5.99 Drug repurposing for treating lupus nephritis based on transcriptome profiling and autoimmunity-related serological markers. (27th September 2022) - Parodis, I; Lindblom, J; Toro-Domínguez, D; Carnero-Montoro, E; Borghi, MO; Castillo, J; Enman, Y; Repsilber, D; Mohan, C; Alarcón-Riquelme, M; Barturen, G
Abstract : Purpose: Lupus nephritis (LN) is one of the most severe organ manifestations of systemic lupus erythematosus (SLE) and constitutes an important cause of morbidity and death among patients with SLE. The associated renal injury, and ultimately damage, is the result of an immune-mediated process which involves leukocytes, immune complexes, complement and cytokines. We investigated expression quantitative trait loci (eQTLs), the transcriptome and autoimmunity-related cytokines and autoantibodies in patients with LN to gain insights into pathogenesis and identify drug targets. Methods: We analysed differentially expressed genes (DEGs), pathways and their druggability via the Drug Gene Interaction database (DGIdb) in active LN (n=41) versus healthy controls (HC; n=497), and eQTLs in active or past LN (n=87), based on validated (identified in two independent SLE populations) DEGs in SLE (n=350) vs HC (n=497), in whole blood collected within the frame of the European PRECISESADS consortium. Genome-wide RNA-sequencing and genotyping was previously performed by Illumina assays, and serum levels of 17 cytokines and 18 autoantibodies were analysed using a Luminex assay, ELISA, IDS-iSYS and SPAPLUS analyser (Barturen et al. 2021). Results: A total of 6869 significant and validated DEGs were identified in active LN patients compared with HC. Of these, 1010 validated DEGs were tagged to 34 KEGG pathways including 24 DEGs with a fold change (FC) <0.66 or > 1.5, genes of 18 cis-eQTLs and 3 trans-eQTLs, and 1 gene from cytokines that differed significantly between active LN and HC. Moreover, 2446 validated DEGs were tagged to 216 Reactome pathways included 85 DEGs with a FC <0.66 or > 1.5, genes of 21 cis-eQTLs and 5 trans-eQTLs, and 1 gene from cytokines that differed significantly between active LN and HC. These genes could be targeted by 203 different drugs, with the proteasome inhibitor bortezomib interfering with cathepsin B (CTSB) regulation and cyclophosphamide interfering with the regulation of tumour necrosis factor receptor superfamily member 1A (TNFRSF1A) being of particular interest. Conclusions: Integrated multilevel omics analysis in LN revealed a set of enriched pathways of potential interest for future drug investigation. A prospect for proteasome inhibition was implicated.